RESEARCH ON THE IMPACT OF INVESTMENT ON GREEN ECONOMIC EFFICIENCY - BASED ON ANALYSIS OF 21 PROVINCES IN MONGOLIA - Baasandulam Mavidkhaan; Saikhnaa Munkh-Erdene; Erdenetsetseg Baasanjav; Gerelsuren Gaanjuur; Adiyabaatar Gulguu (International Journal of Innovative Technologies in Social Science, 2025)
With globalization and the rapid development of Mongolia’s economy, domestic and foreign investment has become an important force to promote Mongolia’s economic growth and structural optimization. At the same time, Mongolia is facing severe challenges from increasing environmental pollution and tightening resource constraints. Therefore, it is of great significance to research investment how affects the efficiency of Mongolia’s green economy in order to lead economic development and environmental protection in both directions. Based on the panel data of 21 province in Mongolia from 2010 to 2023, this study measured the green economic efficiency of each province, and constructs a panel threshold model to comprehensively test the relationship between investment and efficiency. The results show that investment, environmental investment, and technological development have a positive impact on green economic efficiency, while the employment population has a negative impact on green economic efficiency. This study not only enriches the theory of investment and green growth, but also provides a basis for local governments to formulate differentiated incentive policies. The main conclusions and recommendations are: The characteristics of the relationship between investment and efficiency, with the increase of investment level, the level of technological innovation increases; provinces at different development stages need to adopt differentiated investment policies, and optimize the investment structure and environment, strengthen the guidance and support role of local governments in green development; strengthen the training and introduction of talents in the field of green technology, attract and retain high-tech talents by establishing talent introduction plans, and enhance technological innovation capabilities.